Women Empowerment Through National Afforestation Programme in Andhra Pradesh - Nataraju, M.S.; Shashidhar, R.; Raghavendra, S.M. (Indian Journal of Extension Education, 2013)
The study was conducted by Regional Centre, National Afforestation and Eco-Development Board, UAS, Bangalore in  Forest Development Agency (FDA) of Guntur, Karimnagar, Anantapur, Mahabubnagar and Eluru of Andhra Pradesh to  analyse the socio-economic profile, extent of participation and empowerment status of women under National  Afforestation Programme (NAP). Majority of the women respondents were middle aged, illiterate and agriculture was the  main occupation. The extent of participation of women in FDA activities showed that more than half of the women  members (68%) were involved occasionally in nursery activities under afforestation work. Majority of the women  members did not attend any kind of workshops, training programmes, demonstrations and educational tour. However,  more than three fourth of the women members (78%) occasionally participated in the group discussions. Nearly half of the  women, regularly participated in FDA activities, attended the management committee meetings and offered suggestions  regularly in the meetings. Empowerment status of women analyzed based on the income generation, employment status  and additional employment generation indicated a steady increase in the income level and decrease in unemployment  status among the women after joining Vana Samrakshana Samiti (VSS) in forest fringe villages of Andhra Pradesh.
Keywords: Afforestation; forest development agency; women empowerment